Influencia del acceso a dispositivos tecnológicos con el nivel de logro en ciencias sociales en estudiantes de la I.E. N°6010120 Las Malvinas, Iquitos 2024 - Casanova Torres, Rosa Linda (2025)
The purpose of the research was to determine if there is an influence of access to technological devices with the level of achievement in Social Sciences in students of I.E. N°6010120 Las Malvinas in the city of Iquitos in the year 2024, so it developed the study with a non-experimental design - quantitative, where the consultation was made to a group of 108 students who were studying in 3rd, 4th and 5th grade of high school of the Educational Institution N°6010120 Las Malvinas, the techniques used were the survey with a questionnaire as an instrument and the documentary review with a data collection sheet as an instrument. Among the results it was found that for each of the dimensions of the variable access to technological devices the students indicated that they use these tools occasionally, and on the variable level of achievement in Social Sciences, the students obtained in the three competencies of the area a rating of expected achievement, so that after performing the analysis of the data using the nonparametric test of Spearman's Rho, the hypothesis of the research was confirmed: “There is influence of access to technological devices with the level of achievement in Social Sciences in students of the I. E. N°6010120 Las Malvinas in the city of Iquitos 2024”, with a significance value (p-value) of less than 0.05.